2012
DOI: 10.1016/j.jacc.2012.03.076
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Myocardial Fibrosis Assessed With Cardiac Magnetic Resonance in Hypertrophic Cardiomyopathy

Abstract: Myocardial fibrosis in HCM is a progressive and fast phenomenon. LGE increment, related to a worse clinical status, is more extensive in apical hypertrophy than in other patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
6
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 31 publications
10
86
6
6
Order By: Relevance
“…Notably, 5 patients showed LGE expansion, and among these none experienced LV-RR and 4 had a decrease in LV ejection fraction ≥10 U during follow-up. Although an increase in LGE extent over time has been recently reported in hypertrophic cardiomyopathy, 28 to the best of our knowledge, this is the first study that indicates that LGE is not fixed but is rather a dynamic process in IDCM, and its increase is associated with progressive LV dysfunction. Cumulating evidence suggests that replacement MF, as detected by LGE technique, occurs as a result of progressive myocyte loss via necrotic, apoptotic, or autophagic cell pathway and alteration of extracellular matrix constituents, 29 which are, in turn, influenced by genetic predisposition, myocardial ischemia, increased wall stress, and activation of renin-angiotensinaldosterone system.…”
Section: Discussionmentioning
confidence: 56%
“…Notably, 5 patients showed LGE expansion, and among these none experienced LV-RR and 4 had a decrease in LV ejection fraction ≥10 U during follow-up. Although an increase in LGE extent over time has been recently reported in hypertrophic cardiomyopathy, 28 to the best of our knowledge, this is the first study that indicates that LGE is not fixed but is rather a dynamic process in IDCM, and its increase is associated with progressive LV dysfunction. Cumulating evidence suggests that replacement MF, as detected by LGE technique, occurs as a result of progressive myocyte loss via necrotic, apoptotic, or autophagic cell pathway and alteration of extracellular matrix constituents, 29 which are, in turn, influenced by genetic predisposition, myocardial ischemia, increased wall stress, and activation of renin-angiotensinaldosterone system.…”
Section: Discussionmentioning
confidence: 56%
“…In a recent study by Todiere et al (99), increases in myocardial LGE were shown in HCM patients during a mean follow-up period of nearly 2 years (Fig 12), predicting worsening clinical status. However, such widespread rapid increase in myocardial fibrosis is likely exaggerated by patient selection bias.…”
Section: Role Of Mr Imaging In Assessing Microvascular Dysfunction Anmentioning
confidence: 87%
“…Myocardial fibrosis, which plays a key role in HCM pathophysiology, could contribute to atrial fibrillation, ventricular tachycardia, LV dysfunction and SCD [24,25,26,27,28,29]. CMR allowed the noninvasive detection and quantification of myocardial fibrosis by LGE.…”
Section: Discussionmentioning
confidence: 99%